2018
DOI: 10.11628/ksppe.2018.21.2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Indoor Foliage Plants and Human Emotions to Indoor Foliage Plants

Abstract: This study was conducted to find out the sensibility reaction and importance with the visual element of indoor foliage plants in the survey of 216 participants. The eight kinds of leaf display plants were purchased and presented on white pot. The eight kinds of plant were included in '50 varieties of indoor foliage plants' announced by NASA and also easy to manage. The correlation between sensibility reaction, importance, loyalty to foliage plants and the expectation of therapeutic effect was investigated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…As a result of examining perceived importance of plant function and value (Table 9), three factors such as esthetics (4.38 ± 0.54), emotional relaxation (4.11 ± 0.76), and environmental (4.01 ± 0.61) showed high importance with the mean higher than 4/5, followed by naturalistic, distinct, and cover. In a study by Jang et al (2018) on the perceived importance according to the visual elements of foliage plants, the importance was highest in environmental, followed by esthetics and emotional relaxation, whereas this study showed a difference in perceived importance, which was highest in esthetics, followed by emotional relaxation and environmental. In 2018 before the outbreak of COVID-19, environmental factors such as fine dust or pollution were perceived as important, but the anxiety and depression caused by the outbreak of COVID-19 for more than 3 years since the end of 2019 may have highlighted the importance of esthetics and emotional relaxation.…”
Section: Perceived Importance Of Plant Function and Valuecontrasting
confidence: 76%
See 1 more Smart Citation
“…As a result of examining perceived importance of plant function and value (Table 9), three factors such as esthetics (4.38 ± 0.54), emotional relaxation (4.11 ± 0.76), and environmental (4.01 ± 0.61) showed high importance with the mean higher than 4/5, followed by naturalistic, distinct, and cover. In a study by Jang et al (2018) on the perceived importance according to the visual elements of foliage plants, the importance was highest in environmental, followed by esthetics and emotional relaxation, whereas this study showed a difference in perceived importance, which was highest in esthetics, followed by emotional relaxation and environmental. In 2018 before the outbreak of COVID-19, environmental factors such as fine dust or pollution were perceived as important, but the anxiety and depression caused by the outbreak of COVID-19 for more than 3 years since the end of 2019 may have highlighted the importance of esthetics and emotional relaxation.…”
Section: Perceived Importance Of Plant Function and Valuecontrasting
confidence: 76%
“…Moreover, not only esthetics but also perceived importance of plants was highest in the group with an average monthly income of 4.01-5 million won among other groups. The fact that the 30s perceive esthetics as most important is supported by Jang et al (2018) who reported in a study on the importance of indoor foliage plants according to visual elements that the 2-30s group attach most importance to esthetics, which includes items such as 'arranging plants so that they blend in with the space', as well as by Jeong and Yang (2022) who reported in a study on the importance of indoor garden plants that the 2-30s consider mood control important. Therefore, considering the characteristics of the subjects is considered highly important in creating landscapes using plants.…”
Section: Ns *mentioning
confidence: 86%
“…In terms of aesthetics, the color of flowers is an important When introducing plants indoors, priority consideration should be given to the benefits that can be obtained through plants, and then the type, shape, and color of plants and pots should be selected to achieve these functions. A previous study (Jang et al, 2018) reported that emotional relaxation is important as well as environmental and aesthetic aspects in the function of indoor plants, and particularly, preference for plants which help increase emotional relaxation and natural healing power is high. That is, in introducing plants indoors, it is necessary to provide contents for management along with components such as plant materials and pots to achieve environmental, aesthetic, and healing functions.…”
Section: Analysis Of Importance and Performance Of Indoor Plant Functionsmentioning
confidence: 99%
“…Hassan et al reported that the elderly had lower blood pressure, felt more comfortable and relaxed, and had lower anxiety levels after the plant task ( 22 ). Plants always have been utilized to release stress and depression and improve mood and psychological stability ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%